Fundamentals of Smart Materials - Shahinpoor, Mohsen (Royal Society of Chemistry, 2020)
Smart materials are of significant interest and this is the first textbook to provide a comprehensive graduate level view of topics that relate to this field. Fundamentals of Smart Materials consists of a workbook and solutions manual covering the basics of different functional material systems aimed at advanced undergraduate and postgraduate students. Topics include piezoelectric materials, magnetostrictive materials, shape memory alloys, mechanochromic materials, thermochromic materials, chemomechanical polymers and self-healing materials. Each chapter provides an introduction to the material, its applications and uses with example problems, fabrication and manufacturing techniques, conclusions, homework problems and a bibliography. Edited by a leading researcher in smart materials, the textbook can be adopted by teachers in materials science and engineering, chemistry, physics and chemical engineering.
Keywords: Smart materials.; Smart materials -- Problems, exercises, etc.; elektronické knihy; electronic books